Propuesta para la implementación de una Caja de Ahorro a los Microempresarios de la Parroquia San Pedro de La Bendita, cantón Catamayo, provincia de Loja - Arias Yaure, Janneth Beatriz (2016)
This project aims to harness the productive potential of microentrepreneurs, by providing funding through the implementation of the savings bank that grants microloans for business investment and in the same way encourage savings; in order to establish, develop and promote forms of development and socio-economic growth, whereas the savings is an autonomous entity based on solidarity and mutual help among those who shape, with a vision towards the future. To fulfill the objectives proposed different methods and techniques applicable to each study was raised. It starts with literature review based on books by relying on information according to the development of the project, related to the popular finance and the process to be followed for an investment project. the socio-economic diagnosis was made, determining some variables (sex-age-education-activity economic-income-expenses) to help establish the current status of each of microentrepreneurs also demand saving and demand was determined by microcredits; no supply because there is no direct competition in the parish for the entity was determined. In designing the technical study the micro location of the Fund was raised, being in the center of the parish, in addition to the distribution of plant and materials and other elements required for the installation and operation of the Savings ; likewise the projected five-year evaluation of the project, administrative and legal study the organizational structure (Mission-Vision-Objectives-Values-logo-slogan), the Savings Bank was designed installed capacity is determined; management structure is a design of structural and functional organization, a manual of functions and manual microcredit; the legal structure includes model statute and rules of procedure of the entity. Regarding the economic-financial study, the investment required for the operation of the entity is detailed, income and expenses, profit and loss, cash flow, consecutively, the techniques of financial evaluation were applied as they are the NPV , TIR, RBC, PRI and sensitivity analysis, positive results, which determine the feasibility to run the project; breakeven applied it in relation to the amount of micro-credit and demand for microcredit. It was concluded that the savings bank is financially feasible and at the same time is primarily recommended to be performed more deposits by partners to thereby increase its capital and will cover all of the needs presented by the partners.Finally, using the methodology, techniques and theoretical contents established studies were completed and the conclusions and recommendations according to the results obtained were also raised; in addition to the bibliography and annexes the format of the surveys, which enabled meet the needs of microentrepreneurs and know the viability of the project is attached; proformas used to determine the fixed assets of the entity, in addition to the design of deposit and withdrawal slips, the model of the credit application also photographs as evidence of fieldwork.